Hypoglycemic encephalopathy: a case series and literature review on outcome determination - Witsch, Jens; Jüttler, Eric (Journal of neurology, 2012)
Data on clinical long-term outcome after the acute phase of hypoglycemic encephalopathy (HE) using validated outcome scales is currently unavailable. Here we report the results of a systematic literature search for studies on HE and data on long-term outcome in patients with HE admitted to three Charité hospitals between January 2005 and July 2010. HE was defined as coma/stupor and blood glucose levels <50 mg/dl on admission, persistence of coma/stupor for ≥24 h despite normalization of blood glucose levels, and exclusion of any other cause of coma/stupor. Outcome was assessed using the modified Rankin scale (mRS), Glasgow Outcome Scale (GOS), and Barthel index (BI). Fifteen patients were included, with a mean age of 60 years (range 29-79). Two were lost to follow-up. Of the remaining 13 patients, six had died (46 %). In the seven survivors, the median mRS score was 0 (range 0-5), median GOS score was 5 (range 2-5), and median BI was 100 (range 0-100). MRIs made in the acute phase were available for three patients and revealed no obvious relation between lesion size or pattern and clinical outcome. To our knowledge, this is the first case series using validated clinical scoring systems to determine clinical long-term outcome after HE. The results suggest that mortality is high, but long-term survival with little or no disability is possible and can be observed in the majority of survivors. Risk of death or poor outcome does not seem to be related to MRI features in the acute phase but rather to other presumably medical factors.